Linear phase FIR filter to compute fetal heart rate variability - Marchon, Niyan; Naik, Gourish (International Journal of Engineering and Technology, 2018)
Continuous monitoring of fetal heart rate (FHR) can detect the well-being of the fetus and thus indicates non-reassuring fetal status. In- vasive fetal electrocardiography (FECG) using the fetal scalp electrode applied to the fetus scalp allows accurate detection of fetal QRS (FQRS) complexes, however with a risk of infection to the fetus. We have proposed a non-invasive fetal heart rate (NIFHR) filtering technique employing finite impulse response (FIR) filters. We applied Fast Fourier Transform (FFT) to the Physionet abdominal ECG (aECG) records and derived the fiduciary edges of the spectrum of the FECG. A FIR band pass filter (BPF) is designed which is a com- posite filter consisting of a high pass filter (HPF) followed by a low pass filter (LPF) in that order. The cut off frequencies of these com- posite filters are the fiduciary edges of the fetal electrocardiography spectrum. A FQRS detector to obtain fetal heart rate variability (FHRV) processes the FQRS signal filtered through these composite FIR filters. It is observed that channel 4 from records r01 and r08 obtained 100% results for sensitivity, positive predictive value and accuracy while, the overall accuracy was 92.21%. This design can also be extended to compute maternal heart rate.Â Â